THE ORIGINS AND WAVES OF TERRORISM - Lech Chojnowski (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The level of publicity on issues related to terrorism means that in opinions of many it has become one of the main problems of the modern world. But in reality, the phenomenon of terrorism has been present in societies almost from the beginning of human history and its perception may not have changed so much over time. The paper presents the genesis and waves of terrorism throughout history, with special emphasis on the beginning of this phenomenon identified with the activity of Sicarii organisation in the first century; the birth of modern terrorism at the end of the 18th century; its intensification in the interwar period and in the second half of the twentieth century.The level of publicity on issues related to terrorism means that in opinions of many it has become one of the main problems of the modern world. But in reality, the phenomenon of terrorism has been present in societies almost from the beginning of human history and its perception may not have changed so much over time. The paper presents the genesis and waves of terrorism throughout history, with special emphasis on the beginning of this phenomenon identified with the activity of Sicarii organisation in the first century; the birth of modern terrorism at the end of the 18th century; its intensification in the interwar period and in the second half of the twentieth century.